2017
DOI: 10.1080/10810730.2017.1347217
|View full text |Cite
|
Sign up to set email alerts
|

Sharing “Sex Secrets” on Facebook: A Content Analysis of Youth Peer Communication and Advice Exchange on Social Media about Sexual Health and Intimate Relations

Abstract: Social media present opportunities and challenges for sexual health communication among young people. This study is one of the first to examine the actual use of Facebook for peer communication of sexual health and intimate relations. Content analysis of 2186 anonymous posts in a "sex secrets" Facebook page unofficially affiliated with a Hong Kong University shows gender balance among posters, inclusiveness of sexual minorities, and frequent sharing of personal experiences in storytelling or advice seeking. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 37 publications
2
14
0
4
Order By: Relevance
“…Future research on sex-related gossip may further illuminate gossip’s role in establishing norms. The findings also support past research that much peer communication about sex is focused on advice-giving (Pariera, 2018; Yeo & Chu, 2017), again highlighting the importance of peers as referents and confidants. This may be beneficial, as sexual communication with peers is negatively associated with expectations that future sexual activity would be stigmatized among peers (Ragsdale et al, 2014).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Future research on sex-related gossip may further illuminate gossip’s role in establishing norms. The findings also support past research that much peer communication about sex is focused on advice-giving (Pariera, 2018; Yeo & Chu, 2017), again highlighting the importance of peers as referents and confidants. This may be beneficial, as sexual communication with peers is negatively associated with expectations that future sexual activity would be stigmatized among peers (Ragsdale et al, 2014).…”
Section: Discussionsupporting
confidence: 87%
“…Montemurro et al (2015) found that women were uncomfortable talking with friends about sex unless they saw the conversation as a way to bond or as a means of support. Sex-related talk between friends also focuses on advice-giving (Pariera, 2018; Yeo & Chu, 2017), suggesting that friends may be important information resources. Generating and reinforcing group norms may be another common function, with one study finding gossip about sexual reputation was a common occurrence (Massar et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…First, research has examined the types and nature of health-related communication on SNS. 10-17,19 Second, research has examined audience engagement with cancer-related information posts on SNS by examining what types of posts receive the most comments, shares, likes, and emoji reactions. 6-8,20-23 This previous research has answered critical questions surrounding the types of cancer-related information available on SNS and differential amplifications of certain kinds of cancer-related information on SNS by way of audience engagement.…”
Section: Discussionmentioning
confidence: 99%
“…This growing body of literature has found that, beyond being a means of accessing social support and sharing their illness-related experiences, people use SNS when seeking advice, opinions, or answers to their health-related questions. 10-17 This type of SNS use occurs, despite patients and health-care professionals having concerns about misinformation on social media 14,17,18 as well as the mixed results of research examining the scientific accuracy of health information provided on SNS. 19 Another focus of cancer communication research has been to understand the quantity, content, quality, and user engagement (eg, likes and comments) in relation to information about cancer on SNS.…”
Section: Introductionmentioning
confidence: 99%
“…As such, virtual space is often considered superior to face-to-face communication when sharing sensitive information (e.g., Andalibi et al, 2016). As a result, sex talk is particularly prevalent on the internet, covering topics ranging from sex education, sexual health, and sexual identity validation to exploration of sexual pleasures (e.g., Chiou, 2006; Kummervold et al, 2002; Pedersen, 2014; Salter, 2016; Yeo & Chu, 2017).…”
Section: Sex Talk Onlinementioning
confidence: 99%